Diving - Hood, R. M. N. (1st International Scientific Conference of Aquatic Space Activities, 2008)
Diving is not considered to be a separate sport by its organising body, the Federation Internationale de Natacion (FINA). FINA governs four forms, or disciplines, of aquatic competition . swimming, diving, synchronised swimming and water polo. Diving was popularised by the Swedes and the Germans in the 18th and 19th centuries. It grew out of the gymnastics principles developed in those nations. The first known book on diving was published in Germany in 1843. Competitive diving began in Britain in the 180.s. In the late 19th century a group of Swedish divers visited Great Britain and gave numerous exhibitions, which stimulated the formation of the first diving organisation, the Amateur Diving Association, in 1901. Diving as an Olympic event was first contested at the 1904 Olympic Games in St. Louis, USA, and its appearance on the Olympic programme in both springboard and platform events has been continuous since 1908. Two new events were added to the Olympic programme in 2000 the Sydney Olympic Games for both men and women, these being synchronised springboard diving and synchronised platform diving. These events consist of two divers leaving the springboard or platform simultaneously and diving together as a mirror image of each other performing the same dive. It has become a firm spectator favourite and is added another component to the highly telegenic sport that diving is.